A Geophysical Investigation of Shallow Deformation Along an Anomalous Section of the Wasatch Fault Zone, Utah, USA - McBride, J.; Stephenson, W.; Thomson, T.; Harper, M.; Eipert, A.; Hoopes, J.; Tingey, D.; Keach, R.I.; Okojie-Ayoro, A.; Gunderson, K.; Meirovitz, C.; Hicks, T.; et al. (The Geological Society of America, 2008)
We report the results of a geophysical study of the Wasatch fault zone near the Provo and Salt Lake City segment boundary. This area is anomalous because the fault zone strikes more east-west than north-south. Vibroseis was used to record a common mid-point (CMP) profile that provides information to depths of ~500 m. A tomographic velocity model, derived from first breaks, constrained source and receiver static corrections; this was required due to complex terrain and significant lateral velocity contrasts. The profile reveals an ~250-m-wide graben in the hanging wall of the main fault that is associated with both synthetic and antithetic faults. Faults defined by apparent reflector offsets propagate upward toward topographic gradients. Faults mapped from a nearby trench and the seismic profile also appear to correlate with topographic alignments on LiDAR gradient maps. The faults as measured in the trench show a wide range of apparent dips, 20°–90°, and appear to steepen with depth on the seismic section. Although the fault zone is likely composed of numerous small faults, the broad asymmetric structure in the hanging wall is fairly simple and dominated by two inward-facing ruptures. Our results indicate the feasibility of mapping fault zones in rugged terrain and complex near-surface geology using low-frequency vibroseis. Further, the integration of geologic mapping and seismic reflection can extend surface observations in areas where structural deformation is obscured by poorly stratified or otherwise unmappable deposits. Therefore, the vibroseis technique, when integrated with geological information, provides constraints for assessing geologic hazards in areas of potential development.